Phenotypes of Campylobacter jejuni luxS Mutants Are Depending on Strain Background, Kind of Mutation and Experimental Conditions - Adler, Linda (Public Library of Science, 2014)
Since the discovery that Campylobacter (C.) jejuni produces Autoinducer 2 (AI-2), various studies have been conducted to explore the function and role of AI-2 in C. jejuni. However, the interpretation of these analyses has been complicated by differences in strain backgrounds, kind of mutation and culture conditions used. Furthermore, all research on AI-2 dependent phenotypes has been conducted with AI-2 synthase (luxS) mutants. This mutation also leads to a disruption of the activated-methyl-cycle. Most studies lack sufficient complementation resulting in not knowing whether phenotypes of luxS mutants depend on disrupted metabolism or lack of AI-2. Additionally, no AI-2 receptor has been found yet. All this contributes to an intensive discussion about the exact role of AI-2 in C. jejuni. Therefore, we examined the impact of different experiment settings on three different C. jejuni luxS mutants on growth and motility (37°C and 42°C). Our study showed that differing phenotypes of C. jejuni luxS mutants depend on strain background, mutation strategy and culture conditions. Furthermore, we complemented experiments with synthetic AI-2 or homocysteine as well as the combination of both. Complementation with AI-2 and AI-2+homocysteine significantly increased the cell number of C. jejuni NCTC 11168ΔluxS in stationary phase compared to the non-complemented C. jejuni NCTC 11168ΔluxS mutant. Genetic complementation of both C. jejuni 81-176 luxS mutants resulted in wild type comparable growth curves. Also swarming ability could be partially complemented. While genetic complementation restored swarming abilities of C. jejuni 81-176ΔluxS, it did not fully restore the phenotype of C. jejuni 81-176::luxS, which indicates that compensatory mutations in other parts of the chromosome and/or potential polar effects may appear in this mutant strain. Also with neither synthetic complementation, the phenotype of the wild type-strains was achieved, suggesting yet another reason for differing phenotypes other than communication and methionine metabolism for C. jejuni luxS mutants.